Strategic Disclosure and Stock Returns: Theory and Evidence from US Cross-Listing - Goto, Shingo; Watanabe, Masahiro; Xu, Yan (Review of Financial Studies, 2009)
When a firm exercises discretion to disclose or withhold information (strategic disclosure), risk-averse investors command higher expected returns when expected cash flows decrease, producing a negative correlation between these expectations. Moreover, stock returns exhibit stronger reversal than they do when full disclosure is enforced. We propose a model that makes these predictions and provide consistent evidence using a panel of foreign firms that list American Depositary Receipts (ADRs). We find significant shifts in the time-series properties of stock returns for firms that undergo large changes in disclosure environments, such as those cross-listing on the NYSE/AMEX/NASDAQ and those from less-developed/emerging markets and code-law countries.